Accuracy of a rapid real-time polymerase chain reaction assay for diagnosis of group B Streptococcus colonization in a cohort of HIV-infected pregnant women. (3rd May 2017) - Gouvea, Maria Isabel S.; Joao, Esau C.; Teixeira, Maria de Lourdes B.; Read, Jennifer S.; Fracalanzza, Sergio E. L.; Souza, Claudia T. V.; Souza, Maria José de; Torres Filho, Helio M.; Leite, Cassiana C. F.; do Brasil, Pedro E. A. A.
Abstract: Objective : There are limited data regarding Xpert performance to detect Group B Streptococcus (GBS) in HIV-infected pregnant women. We evaluated the accuracy of a rapid real-time polymerase chain reaction (PCR) test in a cohort of HIV-infected women. Methods : At 35–37 weeks of pregnancy, a pair of combined rectovaginal swabs were collected for two GBS assays in a cohort of sequentially included HIV-infected women in Rio de Janeiro: (1) culture; and (2) real-time PCR assay [GeneXpert GBS (Cepheid, Sunnyvale, CA)]. Using culture as the reference, sensitivity, specificity, positive and negative-likelihood ratios were estimated. Results : From June 2012 to February 2015, 337 pregnant women met inclusion criteria. One woman was later excluded, due to failure to obtain a result in the index test; 336 were included in the analyses. The GBS colonization rate was 19.04%. Sensitivity and specificity of the GeneXpert GBS assay were 85.94% (95% CI: 75.38–92.42) and 94.85% (95% CI: 91.55–96.91), respectively. Positive and negative predictive values were 79.71% (95% CI: 68.78–87.51) and 96.63% (95% CI: 93.72–98.22), respectively. Conclusions : GeneXpert GBS is an acceptable test for the identification of GBS colonization in HIV-infected pregnant women and represents a reasonable option to detect GBS colonization in settings where culture is not feasible.